Garimpeiro de memórias: memórias de Emanoel Araújo - Rohrer, Francisco Wanderlei (2018)
This survey aims to identify, analyze and disseminate the knowledge about the black people based on Emanoel Araújo’s memory, life course and lifework, taking Africanism as plausible for the decrease of racism and discrimination. Besides standing out as a painter and sculpturer, this memory collector is also a notable curator, carver, designer, printmarker, set designer, museologist, collector, cultural enticer. As a sculpturer, he applies constructivist code and makes use of contemporary material and procedure along with archaic primitive features. Emanoel Araújo is a black man who has made a name in art and culture. His first experience in a museum was as the director of Museu de Arte da Bahia, moreover he has headed Pinacoteca do Estado de São Paulo for ten years, where he could promote the leading expositions in the international circuit. Administrator of various initiatives, he worked as Secretary of Culture in São Paulo city. After researches, publications and exhibitions about the historical, cultural and artistic heritage of the black people in Brazil, Emanuel Araújo granted 1100 pieces from his personal collection under a free-lease agreement and founded Museu Afro Brasil. About the methodology used, the study began with analyses of documents in public archives in Bahia and São Paulo, as well as private documents belonging to the artist, family members and friends. After compiling the documents, oral history techniques were used; hence the interview was the basis for data collection in order to rebuild Emanuel Araújo’s memory. Besides numerous meetings with the subject of this survey himself, 70 more interviews were made with representatives of all segments related to Emanuel Araújo as relatives, friends, gallerists, cultural enticers and administrators, editors, teachers, artists, religious people, politicians, people directly related to plastic and visual art, museum employees from Bahia and São Paulo, among others. The results were qualitatively analyzed and showed that, by elaborating Emanuel Araújo’s memory, his successful journey couldn’t protect him from racism for being black. Besides the direction of Museu Afro Brasil, aimed to research, conservation and exhibition of objects concerning the afro-Brazilian cultural universe, the sculpturer writes articles, produces books and goes on with the production of sculptures, undertaking the curatorship of expositions in Brazil and abroad. As a conclusion, the discussion has enabled the comprehension of the sculpturer’s role as a depositary of the Afro-Brazilian cultural legacy in order to decrease racism and try to break resistance towards the black culture